2012
DOI: 10.1021/jp307892s
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Switching of Conductance with Diarylethene-Based Redox-Active Polymers

Abstract: Reversible switching of conductance using redox triggered switching of a polymer-modified electrode is demonstrated. A bifunctional monomer comprising a central electroswitchable core and two bithiophene units enables formation of a film through anodic electropolymerization. The conductivity of the polymer can be switched electrochemically in a reversible manner by redox triggered opening and closing of the diarylethene unit. In the closed state, the conductivity of the modified electrode is higher than in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 57 publications
(84 reference statements)
0
31
0
Order By: Relevance
“…Spectroscopic comparison with model compound 2 ( Scheme ), for which the open state forms H‐aggregates in solution at below 200 K, indicated that the extent of H‐type interactions in the polymer film was substantial and hence rapid excited state deactivation due to Davydov splitting precluded both fluorescence and photochemical switching . The introduction of a phenyl spacer unit between the dithienylethene and the dithiophene units restored the switching functionality of the dithienylethene unit in a polymer film, however, the quantum yield for photochemical switching was still lower than that observed in solution . The use of a methoxystyryl unit in place of the bithiophene unit also allows for electropolymerization with retention of the photo‐ and electrochemical switching properties of the dithienylethene unit, however, this is achieved at the cost of film thickness and poor film stability under UV irradiation .…”
Section: Methodsmentioning
confidence: 99%
“…Spectroscopic comparison with model compound 2 ( Scheme ), for which the open state forms H‐aggregates in solution at below 200 K, indicated that the extent of H‐type interactions in the polymer film was substantial and hence rapid excited state deactivation due to Davydov splitting precluded both fluorescence and photochemical switching . The introduction of a phenyl spacer unit between the dithienylethene and the dithiophene units restored the switching functionality of the dithienylethene unit in a polymer film, however, the quantum yield for photochemical switching was still lower than that observed in solution . The use of a methoxystyryl unit in place of the bithiophene unit also allows for electropolymerization with retention of the photo‐ and electrochemical switching properties of the dithienylethene unit, however, this is achieved at the cost of film thickness and poor film stability under UV irradiation .…”
Section: Methodsmentioning
confidence: 99%
“…The electrochemical studies of switchable diarylethene derivatives have been extended to various systems self‐assembled as monolayers on gold electrodes and numerous polymeric films deposited on electrodes and operating as photochemically controlled electroconductive systems .…”
Section: Diarylethene‐based Photoelectrochemical Switchesmentioning
confidence: 99%
“…In the attempt to bring organic (semi)conducting molecules and photochromic molecules together, several important studies were reported demonstrating that these two varieties of molecules could be mutually advantageous: dyads, multiads, and polymers decorated with photochromic units were synthesized and tested leading to major changes in conductivity and optical properties upon light irradiation [150,157,159,[176][177][178][179][180][181][182].…”
Section: Photochromic Molecules and Organic Semiconductors Incorporatmentioning
confidence: 99%
“…Alongside to the undoubtedly disruptive examples of integration of photochromic molecules into dyads, a remarkable effort has also been devoted to the synthesis of photochromic conjugated conductive polymers as, in principle, any photochromic switching unit conjugated within a π-electron polymer would lead to a modulable conductivity [175,177,178,180,181,184,185]. However, despite the notable advances, these materials suffer from a slow or sometimes even irreversible switching mechanism along with low electrical conductivities.…”
Section: Photochromic Molecules and Organic Semiconductors Incorporatmentioning
confidence: 99%